Pengaruh Pengetahuan, Pendidikan, Pendapatan, dan Usia Pernikahan terhadap Kejadian Anemia Defisiensi Besi pada Ibu Hamil di Kota Taiz-Yaman: The Effect of Knowledge, Education, Income, and Marriage Age on Iron Deficiency Anemia in Pregnant Women in Taiz City-Yemen - Ali, Lamia A. S.; Joewono, Hermanto Tri; Fatmaningrum, Widati; Thabit, Riyadh A. S.; Almothana, Hebah H. M.; Alsoufi, Fardous G.; Abdullah, Aya Ali; Al-Qadhi, Tasnim Mohammed; Hajj, Suha Ali Al; Ahmed, Samar A. A.; Alselwi, Sarah A. D.; Thabet, Habib; Mohammed, Haitham T. S.; Andriani, Linda (Amerta Nutrition, 2024)
Background: Iron Deficiency Anemia (IDA) is one of the most common types of nutritional anemia in pregnant women and is the most dangerous to the mother and fetus; This is because the need for iron for both the mother and the fetus increases gradually during pregnancy and reaches its highest levels at the end of pregnancy. Objectives: The study aimed to identify the effect of education, income, and age of marriage on the anemia of pregnant women in Taiz City-Yemen. Methods: The study was carried out utilizing a quantitative design (Descriptive study). From 3rd November 2023, until 30th January 2024. A simple random selection procedure is used to choose six of Taiz City's 10 primary healthcare facilities.101 pregnant women between the ages of 18 and 42 took part in the study. Results: The findings showed that the low knowledge levels (0-35%) had low Hb levels (9.3 mg/dL) when compared with higher knowledge levels (> 50%) with Hb levels (9.92 mg/dL). Furthermore, those Lower marriage age (<20 Years) had low Hb levels (9.46 gm/dL) when compared to marriage age (>25) with Hb levels (10.81 mg/dL). On the other hand, lower education levels were associated with low Hb levels (8.18 mg/dL) when compared to higher education levels. Conclusions: Findings demonstrated that lower knowledge levels, younger marriage age, lower education, and lower income were associated with lower hemoglobin levels. These factors were linked to a higher prevalence of anemia. Improved education and income levels can lead to better knowledge and management of anemia.